Morphometric Study of Posterior Aspect of Distal End of Human Adult Dry Left Humerus (Bangladesh Journal of Anatomy, 2015)
Context: Humerus is the long bone of upper limb. The aim of this study is to find out valuable normative data of posterior aspect of distal end of human adult dry left humerus that can enrich the anatomists and play an important role to anthropological researchers and forensic experts. It is also important for orthopedic surgeons in surgical reconstruction of distal humeral fracture and correction of congenital and traumatic anomalies.Materials and Methods: A cross sectional analytic type of study was conducted in the department of Anatomy of Sir Salimullah Medical College, Dhaka from July 2011 to Dec 2012. Two hundred left sided humerus were collected from the students of Department of Anatomy of Sir Salimullah Medical College, Dhaka and Dhaka National Medical College, Dhaka. Measurements were taken from posterior aspect of distal end of left humerus by direct physical standard osteometric method and recorded in the metric unit centimeter (cm).Result: The result revealed that the male values were higher than female. The measurements were statistically analysed. There were significant difference (p=0.001) between male and female values.Bangladesh J. Anat. 2015; 13(1) : 11-15